ANALISIS KANDUNGAN FLAVONOID PADA TEH BENALU (Dendropohtoe pentandra (L.) Miq.) - Jecklyn A Lekal; Theopilus Watuguly (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: Benalu is one of the plant species that lives attached to other plants. The parasite is hemiparasit or half parasitic because it has a green leaf substance (chlorophyll) used for the assimilation process and only sucks water and organic matter from its host plant. Flavonoids are phenol compounds commonly found in vascular plants including parasites. Flavonoids are useful for protecting cell structures, increasing the effectiveness of vitamin C, anti-inflammation, preventing bone loss and as an antibiotic. Method: Total flavonoid content in clove parasite tea using UV-Vis Spectrophotometer method. Results: Total flavonoid in tea clove parasite was 0.2819%. Flavonoids found in tea parasite cloves are low with the presence of heating and temperature factors. Conclusion: Based on the quantitative test, leaf parasite is the highest flavonoid level of 13.702% and after being made tea, flavonoid levels changed to 0.281%.